Engineering tomorrow : - Bell, Trudy E. (IEEE Press, 2000)
The rush of technology in the 20th century brought more advances than the 11th through 19th centuries combined. Automobiles and aircraft, television and radio, computers and global communications, medical imaging and the leap of humans beyond Earth's atmosphere -- all these were born from the creative spark and labor of scientists and engineers.